A case of stage IV gastric cancer with para-aortic lymph node metastasis showing pathological complete response after neoadjuvant chemotherapy - Yuki Katsura; Takehiro Okabayashi; Manabu Matsumoto; Kazuhide Ozaki; Yuichi Shibuya (Surgical Case Reports, 2020)
Abstract Background Stage IV advanced gastric cancer with para-aortic lymph node metastasis (PALM) is considered unresectable. Systemic chemotherapy is the treatment of choice for such tumors, while conversion surgery may be a treatment option in the case chemotherapy is effective but R0 resection is possible. We report a case of stage IV gastric cancer with PALM that showed pathological complete response (pCR) after neoadjuvant chemotherapy (NAC) using S-1, oxaliplatin, and trastuzumab (SOX+HER). Case presentation A 69-year-old woman who was diagnosed with type 4 stage IV gastric cancer with PALM underwent five courses of NAC with the SOX+HER regimen. The primary tumor and the PALM shrank after treatment, suggesting that the NAC induced a partial response. We performed a total gastrectomy plus distal pancreaticosplenectomy with para-aortic lymph node dissection. Histological analysis revealed no remnant cancer cells in the primary tumor or the lymph nodes, confirming a pCR. The postoperative course was uneventful, and the patient was discharged on day 14 after the operation. S-1 was started as adjuvant chemotherapy, and the patient remains alive without recurrence 2 months after surgery. Conclusion This case shows the possibility of conversion surgery after SOX+HER therapy for stage IV advanced gastric cancer with PALM.